Comparison of Lung Asbestos Fiber Content in Cancer Subjects with Healthy Individuals with no Known History of Occupational Asbestos Exposure in Korea - Han, Jeong Hee; Park, Jung Duck; Sakai, Kiyoshi; Hisanaga, Naomi; Chang, Hee Kyung; Lee, Yong Hwan; Kwon, Il Hoon; Choi, Byung Sun; Chung, Yong Hyun; Kim, Hyeon Yeong; Yang, Jung Sun; Cho, Myung Haing; et al. (Journal of Toxicology and Environmental Health, Part A, 2009)
To evaluate the effects of environmental asbestos exposure on the inducement of lung cancer, pulmonary asbestos and non-asbestos fiber content was determined in 36 normal Korean subjects and 38 lung cancer subjects with no known occupational history of asbestos exposure. Pulmonary asbestos fiber content was measured by transmission electron microscopy (TEM) with energy-dispersive x-ray analysis after applying a low-temperature ashing procedure. Chrysotile fibers were the major fiber type found in the lungs of the Korean subjects. The asbestos fiber concentrations found in the lungs of normal males (25) and females (11) were 0.26 × 10 6 fibers/g of dry lung tissue and 0.16 × 10 6 fibers/g of dry lung tissue, respectively. The asbestos concentrations found in the lungs of cancer subjects were 0.16 × 10 6 fibers/g of dry lung tissue for 32 males and 0.44 × 10 6 fibers/g of dry lung tissue for 6 females. No statistical difference was found in pulmonary asbestos content between the normal and lung cancer subjects, whereas a statistical difference was noted between normal and lung cancer subjects with respect to lung non-asbestos content, indicating a potential role for non-asbestos fibers being associated with lung cancer.